KONDISI SOSIAL EKONOMI BURUH PEMETIK TEH JORONG KAYU JAO KANAGARIAN BATANG BARUS KECAMATAN GUNUNG TALANG KABUPATEN SOLOK - Susanti, Devitri - (Pendidikan Geografi, 2014)
This study aims to get the data, process, analyze and discuss the Socio-Economic Conditions Labour Tea Pickers in Jorong Kayu Jao Kanagarian Batang Barus Kecamatan Gunung Talang Kabupaten Solok. Type of the research is descriptive. Population of study is Tea Pickers Labour Jorong Kayu Jao Kanagarian Barus Kecamatan Gunung Talang Kabupaten Solok. The Samples amounts of research are 70 respondents taken by proportional random sampling technique. The results of study showed : 1) the condition of labor education seen from the tea pickers labor was completed primary school with formal education, child labours tea pickers is a junior high contained 28.12% on weak criteria, 2) Tea pickers health condition is good, the treated place are social health center (PUSKESMAS) with cost of themselves which contained 45.47% on the sufficient criteria, 3) Income conditions of labor tea pickers in one week 54.29% as big as Rp.100.000-200.000 and 54.29% to the revenue side jobs (51.43%) of Rp.50.000-100.000 whenever it works, and (54.29%) said enough with income them receive, 4) conditions of resident tea pickers 45.71% are a wooden house or board with 61.43% said condition its rather good and rather clean.